Quality of life on type 2 diabetes patients in Indonesia: systematic review - Suniyadewi, Ni Wayan; Sufyanti, Yuni; Kurniawati, Ninuk Dian; Buntari, Ni Luh Putu Inca; Rismayanti, Dewa Ayu (Journal of the Pakistan Medical Association, 2023)
Objective: To review various quality of life questionnaires related to patients of type 2 diabetes mellitus. Method: The systematic review comprised search on SAGE, PubMed, ProQuest, Ebsco and Google Scholar databases for studies using quality of life questionnaires related to patients of type 2 diabetes mellitus published between January 2012 and January 2022 in either English or Bhasha language. Data extraction and assessment was done in line with the Preferred Reporting Items for Systematic Reviews and Meta-analyses checklist. Results: Of the 25 studies reviewed, 23(92.2%) were in the English language. They were conducted in 17(51.5%) of the 33 provinces in Indonesia. The questionnaires used were 36-item Short Form 8(32%), EuroQol 5-dimension 5-level scale 6(24%), World Health Organisation Quality of Life-Brief version 6(24%), Diabetes Quality of Life 3(12%) and Diabetes Quality of Life Clinical Trial Questionnaire 2(8%). Variables associated with the quality of life of the diabetics included education, gender and age. The internal factors included glycaemic control, psychological condition, self-efficacy, perception of illness, self-care management, medication adherence, neutrophil-lymphocyte ratio and complications. The external factors included family support, medication counselling and pharmacists’ intervention. Conclusions: Many instruments measure quality of life related to patients of diabetes mellitus. Countries with different socio-cultural forms have different quality of life perspectives, and the assessment tool should be picked accordingly. Keywords: Diabetes mellitus, Glycaemic, Neutrophils, Pharmacists, Self-efficacy, Surgical mesh, Medication adherence, Lymphocytes